H 2 S(g) + 2 O 2 (g) SO 3 (g) + H 2 O(l) H 2 S(g) + 2 O 2 (g) H 2 SO 4 (l) ΔH = kJ H 2 SO 4 (l) SO 3 (g) + H 2 O(g) ΔH = kJ H 2 O(g) H 2 O(l) ΔH = kJ
H 2 S(g) + 2 O 2 (g) SO 3 (g) + H 2 O(l) H 2 S(g) + 2 O 2 (g) H 2 SO 4 (l) ΔH = kJ H 2 SO 4 (l) SO 3 (g) + H 2 O(g) ΔH = kJ H 2 O(g) H 2 O(l) ΔH = kJ kJ
H 2 S(g) + 2 O 2 (g) SO 3 (g) + H 2 O(l) H 2 S(g) + 2 O 2 (g) H 2 SO 4 (l) ΔH = kJ H 2 SO 4 (l) SO 3 (g) + H 2 O(g) ΔH = kJ H 2 O(g) H 2 O(l) ΔH = kJ kJ kJ
H 2 S(g) + 2 O 2 (g) SO 3 (g) + H 2 O(l) H 2 S(g) + 2 O 2 (g) H 2 SO 4 (l) ΔH = kJ H 2 SO 4 (l) SO 3 (g) + H 2 O(g) ΔH = kJ H 2 O(g) H 2 O(l) ΔH = kJ kJ kJ kJ
4 PCl 5 (g) → P 4 (s) + 10 Cl 2 (g) P 4 (s) + 6 Cl 2 (g) → 4 PCl 3 (g) ΔH = kJ PCl 3 (g) + Cl 2 (g) → PCl 5 (g) ΔH = kJ
4 PCl 5 (g) → P 4 (s) + 10 Cl 2 (g) P 4 (s) + 6 Cl 2 (g) → 4 PCl 3 (g) ΔH = kJ PCl 3 (g) + Cl 2 (g) → PCl 5 (g) ΔH = kJ 4 PCl 5 (g) → 4 PCl 3 (g) + 4 Cl 2 (g) ΔH = kJ Flip, x 4
4 PCl 5 (g) → P 4 (s) + 10 Cl 2 (g) P 4 (s) + 6 Cl 2 (g) → 4 PCl 3 (g) ΔH = kJ PCl 3 (g) + Cl 2 (g) → PCl 5 (g) ΔH = kJ 4 PCl 5 (g) → 4 PCl 3 (g) + 4 Cl 2 (g) ΔH = kJ 4 PCl 3 (g) → P 4 (s) + 6 Cl 2 (g) ΔH = kJ Flip
4 PCl 5 (g) → P 4 (s) + 10 Cl 2 (g) P 4 (s) + 6 Cl 2 (g) → 4 PCl 3 (g) ΔH = kJ PCl 3 (g) + Cl 2 (g) → PCl 5 (g) ΔH = kJ 4 PCl 5 (g) → 4 PCl 3 (g) + 4 Cl 2 (g) ΔH = kJ 4 PCl 3 (g) → P 4 (s) + 6 Cl 2 (g) ΔH = kJ 4 PCl 5 (g) → P 4 (s) + 10 Cl 2 (g) ΔH = kJ
N 2 (g) + 3 H 2 (g) → 2 NH 3 (g) 2 NH 3 (g) + 4 H 2 O(l) → 2 NO 2 (g) + 7 H 2 (g) ΔH = kJ 2 NO 2 (g) → N 2 (g) + 2 O 2 (g) ΔH = kJ 2 H 2 O(l) → 2 H 2 (g) + O 2 (g) ΔH = kJ
N 2 (g) + 3 H 2 (g) → 2 NH 3 (g) 2 NH 3 (g) + 4 H 2 O(l) → 2 NO 2 (g) + 7 H 2 (g) ΔH = -57 kJ 2 NO 2 (g) → N 2 (g) + 2 O 2 (g) ΔH = +33 kJ 2 H 2 O(l) → 2 H 2 (g) + O 2 (g) ΔH = kJ 2 NO 2 (g) + 7 H 2 (g) → 2 NH 3 (g) + 4 H 2 O(l) ΔH = +57 kJ Flip
N 2 (g) + 3 H 2 (g) → 2 NH 3 (g) 2 NH 3 (g) + 4 H 2 O(l) → 2 NO 2 (g) + 7 H 2 (g) ΔH = -57 kJ 2 NO 2 (g) → N 2 (g) + 2 O 2 (g) ΔH = +33 kJ 2 H 2 O(l) → 2 H 2 (g) + O 2 (g) ΔH = kJ 2 NO 2 (g) + 7 H 2 (g) → 2 NH 3 (g) + 4 H 2 O(l) ΔH = +57 kJ N 2 (g) + 2 O 2 (g) → 2 NO 2 (g) ΔH = -33 kJ Flip
N 2 (g) + 3 H 2 (g) → 2 NH 3 (g) 2 NH 3 (g) + 4 H 2 O(l) → 2 NO 2 (g) + 7 H 2 (g) ΔH = -57 kJ 2 NO 2 (g) → N 2 (g) + 2 O 2 (g) ΔH = +33 kJ 2 H 2 O(l) → 2 H 2 (g) + O 2 (g) ΔH = kJ 2 NO 2 (g) + 7 H 2 (g) → 2 NH 3 (g) + 4 H 2 O(l) ΔH = +57 kJ N 2 (g) + 2 O 2 (g) → 2 NO 2 (g) ΔH = -33 kJ 4 H 2 O(l) → 4 H 2 (g) + 2 O 2 (g) ΔH = kJ x 2
N 2 (g) + 3 H 2 (g) → 2 NH 3 (g) 2 NH 3 (g) + 4 H 2 O(l) → 2 NO 2 (g) + 7 H 2 (g) ΔH = -57 kJ 2 NO 2 (g) → N 2 (g) + 2 O 2 (g) ΔH = +33 kJ 2 H 2 O(l) → 2 H 2 (g) + O 2 (g) ΔH = kJ 3 2 NO 2 (g) + 7 H 2 (g) → 2 NH 3 (g) + 4 H 2 O(l) ΔH = +57 kJ N 2 (g) + 2 O 2 (g) → 2 NO 2 (g) ΔH = -33 kJ 4 H 2 O(l) → 4 H 2 (g) + 2 O 2 (g) ΔH = kJ N 2 (g) + 3 H 2 (g) → 2 NH 3 (g)ΔH = kJ
3 Fe 2 O 3 (s) + CO(g) → 2 Fe 3 O 4 (s) + CO 2 (g) 2 Fe(s) + 3 CO 2 (g) → Fe 2 O 3 (s) + 3 CO(g) ΔH = kJ 3 FeO(s) + CO 2 (g) → Fe 3 O 4 (s) + CO(g) ΔH = kJ FeO(s) + CO(g) → Fe(s) + CO 2 (g) ΔH = +0.6 kJ
3 Fe 2 O 3 (s) + CO(g) → 2 Fe 3 O 4 (s) + CO 2 (g) 2 Fe(s) + 3 CO 2 (g) → Fe 2 O 3 (s) + 3 CO(g) ΔH = kJ 3 FeO(s) + CO 2 (g) → Fe 3 O 4 (s) + CO(g) ΔH = kJ FeO(s) + CO(g) → Fe(s) + CO 2 (g) ΔH = +0.6 kJ 3 Fe 2 O 3 (s) + 9 CO(g) → 6 Fe(s) + 9 CO 2 (g) ΔH = kJ Flip, x 3
3 Fe 2 O 3 (s) + CO(g) → 2 Fe 3 O 4 (s) + CO 2 (g) 2 Fe(s) + 3 CO 2 (g) → Fe 2 O 3 (s) + 3 CO(g) ΔH = kJ 3 FeO(s) + CO 2 (g) → Fe 3 O 4 (s) + CO(g) ΔH = kJ FeO(s) + CO(g) → Fe(s) + CO 2 (g) ΔH = +0.6 kJ 3 Fe 2 O 3 (s) + 9 CO(g) → 6 Fe(s) + 9 CO 2 (g) ΔH = kJ 6 FeO(s) + 2 CO 2 (g) → 2 Fe 3 O 4 (s) + 2 CO(g) ΔH = kJ x 2
3 Fe 2 O 3 (s) + CO(g) → 2 Fe 3 O 4 (s) + CO 2 (g) 2 Fe(s) + 3 CO 2 (g) → Fe 2 O 3 (s) + 3 CO(g) ΔH = kJ 3 FeO(s) + CO 2 (g) → Fe 3 O 4 (s) + CO(g) ΔH = kJ FeO(s) + CO(g) → Fe(s) + CO 2 (g) ΔH = +0.6 kJ 3 Fe 2 O 3 (s) + 9 CO(g) → 6 Fe(s) + 9 CO 2 (g) ΔH = kJ 6 FeO(s) + 2 CO 2 (g) → 2 Fe 3 O 4 (s) + 2 CO(g) ΔH = kJ 6 Fe(s) + 6 CO 2 (g) → 6 FeO(s) + 6 CO(g) ΔH = -3.6 kJ Flip, x 6
3 Fe 2 O 3 (s) + CO(g) → 2 Fe 3 O 4 (s) + CO 2 (g) 2 Fe(s) + 3 CO 2 (g) → Fe 2 O 3 (s) + 3 CO(g) ΔH = kJ 3 FeO(s) + CO 2 (g) → Fe 3 O 4 (s) + CO(g) ΔH = kJ FeO(s) + CO(g) → Fe(s) + CO 2 (g) ΔH = +0.6 kJ 3 Fe 2 O 3 (s) + 9 CO(g) → 6 Fe(s) + 9 CO 2 (g) ΔH = kJ 6 FeO(s) + 2 CO 2 (g) → 2 Fe 3 O 4 (s) + 2 CO(g) ΔH = kJ 6 Fe(s) + 6 CO 2 (g) → 6 FeO(s) + 6 CO(g) ΔH = -3.6 kJ 3 Fe 2 O 3 (s) + CO(g) → 2 Fe 3 O 4 (s) + CO 2 (g)ΔH = kJ
C 2 H 4 (g) + 6 F 2 (g) 2 CF 4 (g) + 4 HF(g) H 2 (g) + F 2 (g) 2HF(g) H = – 537 kJ C(s) + 2 F 2 (g) CF 4 (g) H = – 680 kJ 2 C(s) + 2 H 2 (g) C 2 H 4 (g) H = kJ
C 2 H 4 (g) + 6 F 2 (g) 2 CF 4 (g) + 4 HF(g) H 2 (g) + F 2 (g) 2HF(g) H = kJ C(s) + 2 F 2 (g) CF 4 (g) H = kJ 2 C(s) + 2 H 2 (g) C 2 H 4 (g) H = kJ 2 H 2 (g) + 2 F2(g) 4 HF(g) H = kJ 2 C(s) + 4 F 2 (g) 2 CF 4 (g) H = kJ C 2 H 4 (g) 2 C(s) + 2 H 2 (g) H = kJ C 2 H 4 (g) + 6 F 2 (g) 2 CF 4 (g) + 4 HF(g) H = kJ
3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g)
½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ
3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g) ½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ H 2 (g) + ½ O 2 (g) → H 2 0(l) ΔH° f = kJ
3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g) ½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ H 2 (g) + ½ O 2 (g) → H 2 0(l) ΔH° f = kJ ½ H 2 (g) + ½ N 2 (g) + 3/2 O 2 (g) → HNO 3 (l) ΔH° f = kJ
3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g) ½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ H 2 (g) + ½ O 2 (g) → H 2 0(l) ΔH° f = kJ ½ H 2 (g) + ½ N 2 (g) + 3/2 O 2 (g) → HNO 3 (l) ΔH° f = kJ ½ N 2 + ½ O 2 (g) → NO(g) ΔH° f = kJ
3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g) ½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ H 2 (g) + ½ O 2 (g) → H 2 0(l) ΔH° f = kJ ½ H 2 (g) + ½ N 2 (g) + 3/2 O 2 (g) → HNO 3 (l) ΔH° f = kJ ½ N 2 + ½ O 2 (g) → NO(g) ΔH° f = kJ 3 NO 2 (g) → 3/2 N 2 (g) + 3O 2 (g) ΔH = -3(ΔH° f ) = kJ Flip, x 3
3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g) ½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ H 2 (g) + ½ O 2 (g) → H 2 0(l) ΔH° f = kJ ½ H 2 (g) + ½ N 2 (g) + 3/2 O 2 (g) → HNO 3 (l) ΔH° f = kJ ½ N 2 + ½ O 2 (g) → NO(g) ΔH° f = kJ 3 NO 2 (g) → 3/2 N 2 (g) + 3O 2 (g) ΔH = -3(ΔH° f ) = kJ H 2 0(l) → H 2 (g) + ½ O 2 (g) ΔH = -(ΔH° f ) = kJ Flip
3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g) ½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ H 2 (g) + ½ O 2 (g) → H 2 0(l)ΔH° f = kJ ½ H 2 (g) + ½ N 2 (g) + 3/2 O 2 (g) → HNO 3 (l)ΔH° f = kJ ½ N 2 + ½ O 2 (g) → NO(g)ΔH° f = kJ 3 NO 2 (g) → 3/2 N 2 (g) + 3O 2 (g) ΔH = -3(ΔH° f ) = kJ H 2 0(l) → H 2 (g) + ½ O 2 (g) ΔH = -(ΔH° f ) = kJ H 2 (g) + N 2 (g) + 3 O 2 (g) → 2 HNO 3 (l)ΔH = 2(ΔH° f ) = kJ x 2
3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g) ½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ H 2 (g) + ½ O 2 (g) → H 2 0(l) ΔH° f = kJ ½ H 2 (g) + ½ N 2 (g) + 3/2 O 2 (g) → HNO 3 (l) ΔH° f = kJ ½ N 2 (g) + ½ O 2 (g) → NO(g) ΔH° f = kJ 3 NO 2 (g) → 3/2 N 2 (g) + 3O 2 (g) ΔH = -3(ΔH° f ) = kJ H 2 0(l) → H 2 (g) + ½ O 2 (g) ΔH = -(ΔH° f ) = kJ H 2 (g) + N 2 (g) + 3 O 2 (g) → 2 HNO 3 (l)ΔH = 2(ΔH° f ) = kJ ½ N 2 (g) + ½ O 2 (g) → NO(g)ΔH = (ΔH° f ) = kJ
3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g) ½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ H 2 (g) + ½ O 2 (g) → H 2 0(l) ΔH° f = kJ ½ H 2 (g) + ½ N 2 (g) + 3/2 O 2 (g) → HNO 3 (l) ΔH° f = kJ ½ N 2 (g) + ½ O 2 (g) → NO(g) ΔH° f = kJ 3 NO 2 (g) → 3/2 N 2 (g) + 3O 2 (g) ΔH = -3(ΔH° f ) = kJ H 2 0(l) → H 2 (g) + ½ O 2 (g) ΔH = -(ΔH° f ) = kJ H 2 (g) + N 2 (g) + 3 O 2 (g) → 2 HNO 3 (l)ΔH = 2(ΔH° f ) = kJ ½ N 2 (g)+ ½ O 2 (g) → NO(g)ΔH = (ΔH° f ) = kJ 3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g)ΔH = kJ
3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g) ½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ H 2 (g) + ½ O 2 (g) → H 2 0(l) ΔH° f = kJ ½ H 2 (g) + ½ N 2 (g) + 3/2 O 2 (g) → HNO 3 (l) ΔH° f = kJ ½ N 2 (g) + ½ O 2 (g) → NO(g) ΔH° f = kJ 3 NO 2 (g) → 3/2 N 2 (g) + 3O 2 (g) ΔH = -3(ΔH° f ) = kJ H 2 0(l) → H 2 (g) + ½ O 2 (g) ΔH = -(ΔH° f ) = kJ H 2 (g) + N 2 (g) + 3 O 2 (g) → 2 HNO 3 (l)ΔH = 2(ΔH° f ) = kJ ½ N 2 (g)+ ½ O 2 (g) → NO(g)ΔH = (ΔH° f ) = kJ 3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g)ΔH = kJ ΔH = [2(ΔH° f ) + ΔH° f ] – [3(ΔH° f ) + ΔH° f ]